Sex differences in psychological distress, behavioural and emotional problems, and substance use in young people in out‐of‐home care. Issue 2 (8th August 2019) - Cotton, Sue M.; Rice, Simon; Moeller‐Saxone, Kristen; Magnus, Anne; Harvey, Carol; Mihalopoulos, Cathy; Humphreys, Cathy; Murray, Lenice; Halperin, Steve; McGorry, Patrick D.; Herrman, Helen
Abstract: The aim of the study was to examine sex differences in self‐reported psychological distress, behavioural and emotional problems, and substance use in young people living in out‐of‐home care (OoHC). One hundred seventy‐six young people aged 12–17 years (females 53.4%) in OoHC in metropolitan Melbourne, Australia, were interviewed. Participants completed self‐report measures: Kessler Psychological Distress Scale, Strengths and Difficulties Questionnaire, and the World Health Organization Alcohol, Smoking, and Substance Involvement Screening Test—Youth Version. Girls had more OoHC placement instability over the past year compared with boys ( p  = .019). Compared with boys, the girls had significantly higher levels of distress ( p  < .001) ( p  = .007), were more likely to have self‐reported emotional symptoms ( p  < .001) and peer relationship problems ( p  = .043) and were more likely to use sedatives ( p  = .004). Girls had more psychological distress, behavioural disturbance, and sedative abuse; placement instability might contribute to these problems. Greater integration across OoHC, mental health, and substance use sectors is required. Girls in OoHC may benefit from interventions targeting problems with peer relationship and substance use and supporting prosocial behaviour; such targets may reduce distress and emotional symptoms and possibly prevent longer term problems.